All-electron spin–orbit configuration interaction study on the valence and low-lying Rydberg electronic states of GeH. (May 2015) - Li, Rui; Zhai, Zhen; Zhang, Xiaomei; Jin, Mingxing; Xu, Haifeng; Yan, Bing
Abstract: Germanium monohydride (GeH), an important radical for the growth of semiconductor germanium film, has received much attention. However, the electronic structure and spectroscopic properties of low-lying excited states of the radical have not been well understood, especially the coupling between different electronic states. In this work, eight Λ–S valence states and four low-lying Λ–S Rydberg states correlated to the four lowest dissociation limits of GeH are investigated by employing the multireference configuration interaction method. With the inclusion of spin–orbit coupling effect, there are 24 Ω states generated from 12 Λ–S states. On the basis of computed potential energy curves of the Λ–S and Ω states, the spectroscopic parameters of bound states are evaluated, which demonstrate that the first Rydberg state 3 2 Σ + located at 5.12 eV is exactly the B 2 Σ + state tentatively assigned by experiment. With the help of the calculated spin–orbit matrix elements, the predissociation mechanism of A 2 Δ state is investigated, which may interpret the fact that ν′>2 vibrational levels of A 2 Δ state are difficult to be detected in experiment. Finally, the transition dipole moments and the radiative lifetimes of several vibrational levels of A 2 Δ and a 4 Σ − states are calculated. Highlights: The PECs of GeH were computed with the MRCI method. The spin–orbit coupling effect was considered in the calculations. The spectroscopic constants of Λ–S and Ω states of GeH were fitted. The predissociation mechanisms of A 2 Δ, 2 2 Σ + and 3 2 Σ + states were discussed. The radiative lifetimes of A 2 Δ and a 4 Σ − states of GeH were evaluated.